2022
DOI: 10.1111/prd.12440
|View full text |Cite
|
Sign up to set email alerts
|

Minimal invasiveness at dental implant placement: A systematic review with meta‐analyses on flapless fully guided surgery

Abstract: Edwin Ruales-Carrera and Sofya Sadilina contributed equally to this study.on the basis of language, date of publication, publication status, length of follow-up, or number of included patients/arms. | Information sourcesTwo review authors (MR and ER) performed in duplicate the systematic search in four electronic (Medline via PubMed, CENTRAL, Scopus, Web of Science) and gray literature (OpenGrey; www.openg rey.eu) databases, without language restrictions from outset to 4 October 2021. The complete search strat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 38 publications
(524 reference statements)
0
14
0
1
Order By: Relevance
“…51 Furthermore, this systematic review did not consider outcomes such as implant survival, patient-reported outcome measures, incidence of peri-implant diseases, costs, and esthetics, despite their potential influence on decision-making. 52 Finally, it is important to note that the evaluation of bone reconstructions in severely resorbed sockets fell beyond the scope of the present review.…”
Section: Discussionmentioning
confidence: 97%
“…51 Furthermore, this systematic review did not consider outcomes such as implant survival, patient-reported outcome measures, incidence of peri-implant diseases, costs, and esthetics, despite their potential influence on decision-making. 52 Finally, it is important to note that the evaluation of bone reconstructions in severely resorbed sockets fell beyond the scope of the present review.…”
Section: Discussionmentioning
confidence: 97%
“…Publication bias was investigated through funnel plot visualization. This was possible because all meta‐analyses had <10 studies included, thus preventing the use of the Egger's and Begg's tests 25 …”
Section: Methodsmentioning
confidence: 99%
“…This was possible because all meta-analyses had <10 studies included, thus preventing the use of the Egger's and Begg's tests. 25 3 | RESULTS…”
Section: Risk Of Bias Across Studiesmentioning
confidence: 99%
“…A modern patient-centered focus of implant dentistry lies on less invasive treatment options in order to reduce treatment time (Frizzera et al 2021), patient morbidity (Romandini et al 2022), and costs (Pauletto et al 2021). Especially the use of shorter implants to entail a lower risk for potential damage of neighboring structures and to bypass bone augmentation procedures in atrophic jaws has reduced both complications and patient morbidity (Thoma et al 2017; Romandini et al 2022). While short dental implants were shown to perform well over short periods (Sahrmann et al 2016; Thoma et al 2021), long-term observations are still lacking.…”
Section: Introductionmentioning
confidence: 99%